Novel Design and Simulation of Fuzzy Controller for Turn-On & Turn-Off Angle in Coordination with SRM Speed Control for Electric Vehicles - M Naveen Kumar; R Chidanandappa (Indonesian Journal of Electrical Engineering and Informatics (IJEEI), 2022)
In current scenario the Switch Reluctance Motor (SRM) are powerful alternative for Electric vehicles applications, due to its simple and rugged structure, high speed, its fault tolerance ability and Magnet free design these attributes make SRM superior to other conventional machines. This motor is a reluctance torque-driven stepper motor that can be used for bi-directional control and self-starting applications. In This paper novel control strategy proposed is to minimizing the Multiobjective function for accurate speed control of SRM by using Mamdani based two input two output fuzzy controller for optimal evaluation of α and β angle by designing closed loop system for accurate speed control of SRM and the corresponding error indices ITAE, IAE, ISE for with and without controller is analysed and compared modelling and simulation is done using MATLAB 2020a.